Analisis Daya Dukung Fisik, Riil dan Efektif Ekowisata di Pulau Pisang, Kabupaten Pesisir Barat - Sofiyan, Ade; Winarno, Gunardi Djoko; Hidayat, Wahyu (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
Pisang Island is one of the leading objects of tourist destinations in Pesisir Barat Regency, Lampung Province and has a good potential to be developed for ecotourism. The present problems are the tourist visits that caused disruption and decline in the environmental quality it is important to know the maximum limit of tourist visits to prevent environmental damage. The purpose of this study was to analyze the carrying capacity of the ecotourism sites. The study was conducted in June 2018 - January 2019. The research method used a geographic information system (GIS). The tourism track data that was taken using a global positioning system (GPS) tracker processed using Arc Gis 10.3. The data obtained was then calculated to determine the ecotourism's physical, real and effective carrying capacity. The results revealed that the physical carrying capacity at Pulau Pisang was 175,000 individuals/day, while for real and effective carrying capacity were 27,887 individuals/day and 744 individuals/day respectively. The number of visitors who visit during working days was below the carrying capacity. However, the visit was over the carrying capacity during a holiday such as Idul Fitri days. Therefore, it is necessary to limit visitors during holidays so that environmental sustainability and the comfort of the visit could be maintained. Keywords: ecotourism area, physical, real, effective carrying capacity, Pisang Island